Investigating Netizen Sentiment Toward Halal Certification in Indonesia Using Machine Learning - Yan Putra Timur; Ririn Tri Ratnasari; Anwar Allah Pitchay; Usman Jamilu (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT This study examined the most discussed halal certification terms and topics on Indonesian Twitter. This study also explored the sentiments and opinions of Indonesian netizens on halal certification. This analysis uses Twitter tweets from April 10 to 24, 2023. A quantitative method was used by using Orange Data Mining. Researchers used the keywords "Sertifikasi Halal", "Label Halal" and "Halal MUI" to obtain 1,000 tweets. The results of the study show that the tweets with the highest number of likes and retweets discuss the ease of obtaining Halal certification, which is guaranteed by the Cipta Kerja Law. In addition, the words "halal", "certification", and "MUI" are the most frequently used words in Twitter conversations. The most discussed topics by netizens about halal certification include "halal", "certification", "food", "MUI", "product", "sucofindo", "permit", and "safe".  Twitter is dominated by tweets with neutral sentiments shown by joy emotions, as much as 68.22% of the total tweets. Keywords: Halal certification, sentiment analysis, Twitter, Machine learning, Orange data mining   ABSTRAK Penelitian ini bertujuan untuk menemukan kata-kata dan topik yang paling banyak dibicarakan tentang sertifikasi halal di Twitter Indonesia. Serta untuk menemukan sentimen dan emosi netizen Indonesia tentang sertifikasi halal. Data penelitian ini berasal dari tweet Twitter yang diambil dari 10 April 2023 hingga 24 April 2023. Metode kualitatif dilakukan dengan bantuan Orange Data Mining. Peneliti menggunakan kata kunci "Sertifikasi Halal”, "Label Halal”, dan "Halal MUI” untuk mendapatkan 1.000 tweet. Hasil penelitian menunjukkan bahwa tweet yang memiliki jumlah like dan retweet terbanyak membahas tentang kemudahan perizinan sertifikasi halal yang dijamin dalam UU Cipta Kerja. Selain itu, kata "Halal", "Sertifikasi", dan "MUI" merupakan kata yang paling sering muncul dalam percakapan di Twitter. Topik yang paling banyak diperbincangkan oleh warganet mengenai sertifikasi halal antara lain topik "halal", "sertifikasi", "makanan", "MUI", "produk", "sucofindo", "izin", dan "aman".  Twitter didominasi oleh tweet dengan sentimen netral yang ditunjukkan dengan emosi kegembiraan sebanyak 68,22% dari total tweet. Kata Kunci: Sertifikasi Halal, Sentiment Analisis, Twitter, Machine Learning, Orange Data Mining